EMPOWERED VOICES: A FEMINIST DISCOURSE ANALYSIS OF SELF-LOVE AND CONFIDENCE IN SELENA GOMEZ’S “WHO SAYS” - Syarifah Syarifah (JOURNAL OF EDUCATION SCIENCE, 2025)
Popular music often serves as a subtle site where emotion and ideology intertwine. In Selena Gomez’s “Who Says,” lyrical vulnerability transforms into resilience, crafting a discourse where the female voice reclaims its worth. Within this context, the song operates as a medium of feminist self-articulation that negotiates the boundaries between self-doubt and empowerment. This study aims to examine how Gomez’s lyrics construct self-love and confidence as feminist agency through discursive strategies. Guided by Feminist Critical Discourse Analysis (Lazar, 2020, 2023), supported by hooks’ (2000) notion of self-love as political resistance, and informed by Butler’s (2022) view of performative subjectivity and Gill’s (2021, 2023) theorization of confidence culture and postfeminist affect, the study employs a qualitative textual approach. The analysis identifies three discursive patterns: repetition as resistance, pronoun shifts as collective identity, and rhetorical questioning as empowerment. Findings reveal that repetition reclaims the voice of self-worth, pronoun shifts dissolve the line between the individual and collective self, and rhetorical questions destabilize patriarchal authority. These patterns turn pop lyricism into an act of feminist redefinition. Ultimately, “Who Says” emerges as a lyrical manifesto of self-love—transforming the language of insecurity into affirmation and redefining agency as the right to exist beautifully and unapologetically. Keywords: agency, discourse, empowerment, feminism, music, self-love